Machiavellian Behavior in Auditor Ethics and Professionalism: Cognitive Moral Development Study Approach - Suham Cahyono; Erina Sudaryati (Faculty of Economics, Universitas Internasional Batam, 2023)
Purpose - Machiavellianism, which has a negative effect, can undermine the integrity and objectivity of an auditor when inspecting conduct. Those who behave in this way can have an impact on reducing the quality of the auditor's reporting to top management. Therefore, this study aims to review Machiavellian behavior in auditor ethics and professionalism through the Cognitive Moral Development (CMD) approach. To the best of the author's knowledge, this is the first study that comprehensively discusses Machiavellianism in auditors, both in terms of ethics and professionalism, and through the Cognitive Moral Development approach. Previous studies have not examined this relationship. Research Method - The authors utilize research using a conceptual paper (qualitative approach) to reveal how Machiavellian behavior in auditors has been proven accurate by various previous studies. The study also acknowledges CMD studies as a fundamental basis for developing ethics and professionalism in accordance with the criteria for assigning auditors to companies. Findings - The authors have found that a dysfunctional audit process reduces the quality of audit results, which may decrease public confidence in the auditing profession. Therefore, Machiavellian attitudes among auditors can lead to negative consequences, including unethical behavior. To prevent auditors from acting unethically, it is crucial to promote basic values and norms within the auditing profession, especially based on the accountant's code of ethics as a source of ethical guidance for auditors. Implications - This study has significant implications both theoretically and practically in several ways. The theoretical implications of the author's study provide a broad range of literature on the philosophy of accounting and ethics, particularly how to connect Machiavellian behavior with the ethical and professional external auditor code of conduct. From a practical perspective, this study presents significant evidence for the auditor code of ethics in the auditor framework of professional knowledge.